Caracterización de estructuras celulares cilíndricas con diferentes perfiles radiales de densidad (2021)
The internal structures of the antlers of deer and elk have the characteristic of being cellular structures, which are constituted by a thin region of solid bone in the outer zone of the antlers, and a porous region throughout the interior. Furthermore, the porous region has a pattern of holes that is not constant, but varies randomly in a radial way, from a lower density value, in the center, to a maximum density value, at the ends. This type of geometry is also found in the long bones of humans and other animals, that is, structures designed to withstand impacts and load conditions that require a high energy absorption capacity. This work aims to propose cylindrical geometries, with circular hole patterns, that simulate the horns of deer and elk, but with the difference that they are not random. Different hole patterns, or different radial density profiles, are then to be tested. It is expected to be able to characterize each of the proposed geometries, in order to analyze the effect of said profiles on the mechanical properties of the structures. Likewise, it is intended to find advantages and disadvantages of these geometries compared to their totally solid counterparts. The results of this study suggest that, for the selected manufacturing parameters, the specimens with density profiles show greater stiffness and resistance when the distribution of the holes is uniform and orderly.